Hair glucocorticoids and resting-state frontal lobe oxygenation: Findings from The Irish Longitudinal Study on Ageing - Kenny, Rose; Feeney, Joanne (My University, 2021)
Cerebral blood flow and oxygenation are crucial for maintaining healthy brain structure and function, with hypoperfusion and hypometabolism associated with neurodegenerative and neuropsychiatric conditions. Chronic stress and elevated cortisol have also been associated with cognitive decline, poor mental health and peripheral vascular and cerebrovascular changes. It is plausible that glucocorticoids could alter brain structure and function through increased vulnerability to hypoperfusion and reduced oxygenation. The aim of the current study was to investigate the association between hair glucocorticoids (GCs) and frontal lobe oxygenation using near-infra red spectroscopy (NIRS) in a population sample of 1078 older adults. Data from Wave 3 of The Irish Longitudinal Study of Ageing was analysed. Hair samples were taken for the analysis of glucocorticoids and NIRS was used to measure frontal lobe oxygenation. After both minimal and full adjustment for covariates, hair cortisol and the cortisol-to-cortisone ratio were associated with lower Tissue Saturation Index (TSI; cortisol: B = 0.37, CI 0.60 to 0.14, p = .002; ratio: B = 0.43, CI 0.70 to 0.16, p = .002). Cortisone was not significantly associated with TSI (B = 0.17, CI 0.55 to.21, p = .388). The finding of an inverse relationship between frontal lobe oxygenation and GCs as assessed over a period of months may indicate that reduced oxygenation is one pathway through which chronically elevated GCs affect brain health and function. However, no causality can be inferred from the current data and prospective studies are required to interrogate this.
PUBLISHED
cited By 0
Keywords: Cerebral oxygenation; Glucocorticoid; Aging; Brain; Stress; Ageing